Long-Term Stability Comparison between an Original and a Generic Version of Piperacillin/Tazobactam in Dextrose 5 % Infusion Polyolefin Bags at 5 ± 3 °C after Microwave Freeze-Thaw Treatment - Huvelle Sophie; Godet Marie; Galanti Laurence; Closset Mélanie; Bihin Benoît; Jamart Jacques; Hecq Jean-Daniel (De Gruyter, 2018)
Piperacillin-Tazobactam is frequently infused in hospitals. The use of a generic version was considered after the out of stock of the brand name Tazocin®. The stability of 4 g of Tazocin® in 120 mL of dextrose 5 % (D5) was demonstrated during 35 days at 5 °C ± 3 °C after freezing (−20 °C) and microwave thawing (FMT). The aim of the study was to investigate and compare the long-term stability of Tazocin® and a generic product in the same conditions.